Does internal migration improve overall well-being in Ethiopia? - de Brauw, Alan; Mueller, Valerie; Woldehanna, Tassew (International Food Policy Research Institute, 2013)
In this paper, we use a unique panel dataset of tracked migrants and non-migrants that originate from 18 villages in Ethiopia to examine the welfare impacts of internal migration. Using a number of techniques and various objective and subjective measures, we measure the impacts of migration on the welfare of migrants versus non-migrants. We find large gains to objective welfare measures such as consumption, around 110 percent. Gains are larger among male and urban migrants. Howev-er, we also find that relative to household heads subjective welfare measures are similar for migrants. The large welfare gains to migration suggest that barriers exist, even within countries such as Ethiopia, against the free movement of people to places where they would be objectively better off.